Physical Activity and Knowledge about Nutrition in Adolescents at Madrasah Aliyah Negeri (MAN) Surabaya City - Zulkipli Zulkipli; Nurwijayanti Nurwijayanti; Byba Melda Suhita (Health Dynamics, 2024)
Adolescents are a window of opportunity for future development, so it is necessary to invest in the health and welfare of adolescents in accordance with the Adolescent Nutrition Program launched by the Indonesian government to adjust the Sustainable Development Goal at the UN meeting with a communication strategy for social change and adolescent behavior. This study used a quantitative design with 196 respondents whose samples were taken with probability sampling techniques in the form of simple random sampling. Physical activity data was taken from the International Physical Activity Questionnaire (IPAQ), data on knowledge of nutrients obtained from the Self Administere Qustionnaire (QuesCa) and intensity of fastfood consumption obtained from the Food Frequency Questionnaire while nutritional intake through 24-hour food recall form. Data analysis used multiple linear regression with SPSS 25 statistical tools. Based on the t test, it was concluded that there was an effect of physical activity and knowledge of nutrients with a significance value of 0.000 for each of the two variables. While the intensity of fastfood consumption has a significance value of 0.968 (more than 0.05) which concludes that there is no effect of the intensity of fastfood consumption on nutritional intake. Nutrient knowledge is the factor that most influences nutrient intake with a t-statistic of 5.941. In this study, it was concluded that there was an effect of physical activity and nutritional knowledge on nutritional intake, while the intensity of fastfood consumption did not affect nutritional intake. The dominant factor affecting nutritional intake in this study was nutritional knowledge.